An investigation into strain rate dependent constitutive properties of a sandwiched epoxy interface. (15th December 2016) - Verma, Devendra; Exner, Matthias; Tomar, Vikas
Abstract: A composite material fracture strength can significantly depend on the constitutive description of interfaces. A computational model of composite deformation should, therefore, incorporate interface constitutive behavior. However, separating main phase constitutive behavior from interface constitutive behavior in mechanical property measurement experiments is an arduous task. In this work, an epoxy interface is analyzed under quasistatic and dynamic loading conditions to obtain a description of interfacial constitutive response at strain rates from 10 − 2 to 10 3 s − 1 . The approach relies on describing interfaces as a confined material phase between two unconfined phases. Dynamic microscale impact tests are used to obtain stress-strain response as a function of strain rate for the analyzed interface. The rate dependent stress-strain response is fitted to the Johnson-Cook constitutive model. Based on the analyses of confinement effects, a power law constitutive model is proposed to predict the interface deformation behavior with a dependence on both strain rate and interface thickness. Graphical abstract: Highlights: The stress-strain behavior of 2 µm to 10 µm-thick epoxy interfaces between glass plates is examined. Proposed model captures well the lateral stress (confinement) and strain rate effects during indentation of glass-epoxy interfaces. An analytical model is also proposed to predict the lateral stress during indentation experiments.